Brief Reviews of Books and Products: Chokepoint capitalism - Marco Schirone (Journal of Librarianship and Scholarly Communication, 2023)
This is a book review of: Giblin, R., & Doctorow, C. (2022). Chokepoint Capitalism. Beacon Press. 312 pp., ISBN 978-080700706-8, 26.95 USD (hardcover); ISBN 9780807007075 (ebook).